Pengaruh Ekstrak Etanol Daun Murbei (Morus Alba L.) dengan Glibenklamid Terhadap Ekspresi Gen CYP3A4 pada Kultur Sel HepG2 - Nuralih, Nuralih; Churiyah, Churiyah; Pambudi, Sabar; Tamat, Swasono R.; Meila, Okpri (Universitas Muhammadiyah Surakarta, 2018)
Mulberry leaf is a traditional herb and predicted has ecdysteronecompound which act as antihyperglicemid. Glybenclamide is a synthetic medicine used to cure diabetes mellitus type 2. The leaf reported as competitive inhibitor of CYP3A4 enzyme, which metabolizingglibenclamide. However, in many cases, combination of herbs with synthesis drugs causes interaction if used at the same time. This research aimed to see interaction of ethanol mulberry leaf extract with glibenclamide through CYP3A4 gene expression in HepG2 cell culture.Sample of mulberry extract, glibenclamide, and combination both sample were tested into cell HepG2 culture. Then RNA were isolated and purification using real time PCR to see the gene CYP3A4 expression. As a result, mulberry extract acts as inhibitor enzyme CYP3A4, while glibenclamide is enzyme substrate.The combination of mulberry and glibenclamide showed increased of expression of CYP3A4 gene, means greater enzyme produced, and lower medicine on blood plasma.